PENGARUH CAR, NPL, LDR, GROWTH DEPOSIT DAN BANK OWNERSHIP TERHADAP NIM DENGAN BANK SIZE SEBAGAI VARIABEL KONTROL (Studi Empiris pada Bank Konvensional yang Terdaftar Pada Bursa Efek Indonesia Periode 2010-2014) - Fathinna, Sarah Dewi; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2016)
This research aims to test the influence of Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, Growth Deposit, and Bank Ownership to Net Interest Margin, with using Bank Size as control variable to compare the difference between using Bank Size as control variable and not using Bank Size as control variable.Research population in this paper is Banking listed in IDX 2010-2014 period and the amount of the banks is 30 not-liquidated banks by IDX and Bloomberg. Analysis technique used by this research is Pooled Panel OLS (Ordinary Least Square) with F-statistic test, t-statistic test, classic assumption test such as Normality test, Autocorrelation test, Heteroscedasticity test, and Multicolinearity test. Results show that CARÂ  and LDR have positive and significant to NIM, NPL and Growth Deposit have negative and significant to NIM, Bank Ownership has positive and not significant to NIM.